Hydrogen Tunneling in Thiobenzamide: A Case Study on Tunneling Through High-Energy Barriers - Roque, Jose P. L.; Nunes, Claudio M.; Ntungwe, Epole; Fernandez-Ramos, Antonio; FAUSTO, RUI (American Chemical Society, 2025)
A few intriguing hydrogen quantum mechanical tunneling (QMT) reactions through high-energy barriers (>20 kcal mol-1) have been observed in cryogenic matrices. Building on these examples, we report here investigations into the QMT reactivity of thiobenzamide. Thiol isomers (1Tl) were generated in an argon matrix at 10 and 20 K. One thiol isomer (1Tl-aT) converts into another (1Tl-sT) via QMT S-H rotamerization. Furthermore, thiol isomer 1Tl-sT converts into the thione form (1Tn) through QMT H-shift tautomerization, with a half-life of similar to 180 h, despite a computed barrier of similar to 25 kcal mol(-1). Computed CVT/SCT rate constants at the MPWB1K/6-31+G(d,p) level closely reproduce the experimental data. Remarkably, computations extended to higher temperatures indicate that even at 300 K the H-shift tautomerization is entirely governed by QMT (>99.9%), with a predicted half-life of similar to 1 min. At 200 K, the rate constant decreases by over 2 orders of magnitude. These findings reveal an exceptional reaction model for exploring QMT-governed reactivity under solution conditions and for providing new insights into harnessing QMT in molecular design.
Keywords: Molecular-Orbital Methods